The role of sports in the system of general physical education - Abdurahmonova Bahora (Zien Journals, 2022)
The article analyzes the main approaches to the use of sports games in the school physical education system. The most important purpose of sports in secondary school is to acquaint students with the types of sports games and exercises, to lay the foundation for the right technique.
Keywords: sports games; physical culture; physical development; school physical education system